Design of monitoring system for photovoltaics performance verification plant in Project Las Nubes - Sánchez-Ortiz, Hugo Andrés (Instituto Tecnológico de Costa Rica, 2015)
The present report describes the design of a monitoring system for the Photovoltaics Performance Verification that will implemented in Project Las Nubes, developed by the author of this thesis within the Sustainable Energy Initiative and Project Las Nubes inside the Faculty of Environmental Studies of York University based in Toronto, Canada. Tropical zone has a good conditions for the implementation of photovoltaic energy. However, all the information provided by the manufacturer is obtained under ideals conditions. But the final energy yield of a photovoltaic module has a different behavior under real conditions and the actual performance of photovoltaic cells is unknown at tropical latitudes. This information really meets the requirements of the end user who wants to estimate the pay‐back time of his investment for different module types. For this reason was development a monitoring system that will be implemented in this kind of studies following the standards IEC 61724 and IEC 61853. The hardware can collect the information of the output power and the environmental conditions of the PV module and send the information to the computer for future analysis. The final deliverable is a testing model that is going to be used for further studies. An additional work will be developed designing and a preliminary mounting structure for the Performance Verification Plant.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería en Mecatrónica, 2015.
Keywords: Mediciones eléctricas; Sistemas fotovoltaicos; Prototipo